Vocabulary Lists: Construction Methods and Applications - Angkana Tongpoon Patanasorn (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
It goes without saying that vocabulary plays such a vital role in second language learning. Second language learners find it challenging to communicate and use language effectively without sufficient words. One main objective of language learning and teaching is, therefore, to expand second language learners‟ vocabulary size as efficiently and rapidly as possible in a poor input environment. This group of learners does not have a privilege like their first language counterparts who have opportunities to gradually increase their vocabulary knowledge. In this presentation, roles of vocabulary and vocabulary lists in second language learning will be discussed. Methods in selecting words necessary for second language learners to focus on and for teachers to pay attention to when teaching as well as for curriculum development, instructional materials, and classroom activities will be presented.